2018
DOI: 10.2147/ott.s169531
|View full text |Cite
|
Sign up to set email alerts
|

Significance of PYK2 level as a prognosis predictor in patients with colon adenocarcinoma after surgical resection

Abstract: BackgroundProline-rich/Ca2+-activated tyrosine kinase 2 (PYK2) belongs to the non-receptor tyrosine kinase family, regulates downstream signaling via catalyzing protein phosphorylation. We aimed to investigate clinical significance and mechanisms of PYK2 in colon adenocarcinoma (CAC).MethodsReal time quantitative PCR and immunohistochemistry staining was used to evaluate the expression of PYK2 in clinical CAC tissues. Its association with clinicopathologic characteristics was analyzed by Chi-square test. Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…During the past decades, many efforts have been made to search for biomarkers of COAD. Studies have shown the diagnostic value of DCTN1, DCTN2, and DCTN4 [17] and the prognostic role of LAYN [18], KCNQ1OT1 [19], and PYK2 [20] in COAD, but with limited sample size or inconsistent results. In this study, we analyzed the expression patterns of m 6 A RNA methylation regulators in COAD and their relationship with clinical features by using cohort data from TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, many efforts have been made to search for biomarkers of COAD. Studies have shown the diagnostic value of DCTN1, DCTN2, and DCTN4 [17] and the prognostic role of LAYN [18], KCNQ1OT1 [19], and PYK2 [20] in COAD, but with limited sample size or inconsistent results. In this study, we analyzed the expression patterns of m 6 A RNA methylation regulators in COAD and their relationship with clinical features by using cohort data from TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PYK2 involves autophosphorylation at Tyr-402, which enables the binding of Src via the SH2 domain and phosphorylation of PYK2 at Tyr-579 and Tyr-580, within the kinase domain activation loop, to generate maximal kinase activity (22). Phosphorylated PYK2 functions in the regulation of phagocytosis, migration, proliferation, invasion, oncogenesis and metastasis (21,(23)(24)(25). In macrophages, PYK2 has defined functions in regulating morphology, migration, and phagocytosis (21,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…PYK2 consists of three domains associated with tumor progression and can be activated by multiple growth factors, neuropeptides, cytokines, hormones, and chemokines [10][11][12][13][14][15]. Overexpression of PYK2 has been reported to promote progression and lead to poor prognosis in many kinds of malignant tumors such as breast cancer, liver cancer, lung cancer and pancreatic cancer [7,[16][17][18][19][20][21][22]. PYK2 was only found to serve as an onco-suppressor gene in androgen-dependent prostate cancer cells and neuroblastoma cells so far [23,24].…”
Section: Introductionmentioning
confidence: 99%